The crime of my very existence : Nazism and the myth of Jewish criminality - Berkowitz, Michael (S. Mark Taper Foundation imprint in Jewish studies., 2007)
Berkowitz investigates a dimension of anti-Semitism that was instrumental in the making of the Holocaust: the association of Jews with criminality. He traces the myths and realities about Jewish criminality from the 18th century to the Weimar Republic and on into the Nazi assault upon the Jews.